SYNTHESIS AND EVALUATION OF AN INDUSTRY 4.0 CONTROL ROOM - Hugo, Eduan; Holm, Johann (The South African Journal of Industrial Engineering, 2020)
The technological world is ever-evolving, and industries worldwide must match the pace of inevitable change. We are in the midst of the fourth industrial revolution, and many are suggesting that there may be a fifth industrial revolution in sectors where human interaction is critical. Control rooms are important functional units in many industries, which raises the question of the relevance of Industry 4.0 technologies in the modern-day control room system. A focus area of this study includes defining a generalised operational architecture of a real-world control room with event management functionality — the ‘AS-IS’ model. The impact of intelligent technologies on typical control room operations is modelled holistically (’TO-BE’), and compared with contemporary control rooms to unearth design considerations for future control room development.